2014
DOI: 10.1016/j.joca.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament OsteoArthritis Score (ACLOAS): Longitudinal MRI-based whole joint assessment of anterior cruciate ligament injury

Abstract: ACLOAS allows reliable scoring of acute ACL injury and longitudinal changes. This novel scoring system incorporates features that may be relevant for structural outcome not covered by established OA scoring instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 47 publications
0
102
0
Order By: Relevance
“…Healing traumatic bone marrow lesions and newly developing OA‐associated bone marrow lesions may have different implications for future joint morphology. However, characteristics of the 2 bone marrow lesion types may overlap, posing a challenge for distinct delineation . Although the MOAKS does not distinguish between bone marrow lesion types , the majority of bone marrow lesions observed in the current study demonstrated degenerative characteristics (i.e., located directly subchondral, more circumscribed, and more commonly associated with cartilage damage) .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Healing traumatic bone marrow lesions and newly developing OA‐associated bone marrow lesions may have different implications for future joint morphology. However, characteristics of the 2 bone marrow lesion types may overlap, posing a challenge for distinct delineation . Although the MOAKS does not distinguish between bone marrow lesion types , the majority of bone marrow lesions observed in the current study demonstrated degenerative characteristics (i.e., located directly subchondral, more circumscribed, and more commonly associated with cartilage damage) .…”
Section: Discussionmentioning
confidence: 67%
“…However, characteristics of the 2 bone marrow lesion types may overlap, posing a challenge for distinct delineation (14). Although the MOAKS does not distinguish between bone marrow lesion types (13), the majority of bone marrow lesions observed in the current study demonstrated degenerative characteristics (i.e., located directly subchondral, more circumscribed, and more commonly associated with cartilage damage) (14). The ACL OA Score semiquantitative instrument, recently designed specifically for ACL-injured knees, attempts to overcome this deficiency of the MOAKS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraobserver reliability (kappa) for assessment of effusion‐synovitis for all time points scored was 0.85 (95% confidence interval [95% CI] 0.78, 0.92), and for Hoffa‐synovitis it was 0.54 (95% CI 0.42, 0.66). Interobserver reliability was 0.75 (95% CI 0.66, 0.84) and 0.60 (95% CI 0.48, 0.72), respectively .…”
Section: Methodsmentioning
confidence: 98%
“…All available MRIs were read by a musculoskeletal radiologist (FWR) according to the Anterior Cruciate Ligament OsteoArthritis Scoring (ACLOAS) system . ACLOAS was determined by analyzing nonenhanced MRI scans and using an assessment of inflammation that includes whole‐joint synovitis based on signal changes in Hoffa's fat pad (referred to as Hoffa‐synovitis) and a composite measure of the amount of intraarticular joint fluid and synovial thickening on fluid‐sensitive images (referred to as effusion‐synovitis).…”
Section: Methodsmentioning
confidence: 99%